Evaluating Player Experience in Cycling Exergames - Al-Attas, Rana (Université d'Ottawa / University of Ottawa, 2013)
Obesity has become a worldwide problem that most countries are trying to fight. It affects many people, irrespective of age, race, gender, or religion; anyone can suffer from obesity, which leads to serious problems, both for individuals and for society as a whole. In this study we have selected two groups of people: the basic people who do not exercise on a weekly basis, and the average people who exercise regularly, every week. We have explored the attitude of the two groups in regards to mixing exercises with games, in order to motivate the people with basic activity levels to exercise more frequently. We have used a qualitative standard online questionnaire from AttrakDiff, which evaluates user experience through four important aspects: a) quality; b) subjective understanding of quality and subjective evaluation of quality; c) pragmatic and hedonic features; and d) emotional and behavioural effects. We also did a qualitative study and a quantitative study of some of the important factors present during exercise. The results of the qualitative and quantitative studies were very encouraging as they revealed that mixing games with exercise can transform boring exercises into entertaining ones. It can also motivate players to continue and repeat the exercises. The ANOVA test was applied and it shows that combining games with a stationary bike has a significant effect on the speed and the average rotation per minute of the participants.
Keywords: Evaluation; Exergaming; Player Experience; Interactive Cycling Exergame; Attrakdiff